QUANTITATIVE ESTIMATION OF PYRUVATE IN STILESIA JADHAVE N.SP - JADHAV, B. V.; KHADAP, R. M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2002)
During glycolysis on intermediary anaerobic phase carbohydrate metabolism the glucose is broken into phosphoenolpyruvate. The small quantity of phosphoenol pyruvate is not converted into pyruvate which later reduces to lactic acid. The present paper deals with the quantitative study of pyruvate estimation biochemically and found that cestode parasite Stilesia jadhave n.sp. has significant quantity of pyruvate. The significance of large amount of pyruvate in anaerobic intestinal parasite and various factors of its role is disçussed.